Income inequality and the economic position of women in Norway 1970 - 2002 - Hilde Bojer (University of Oslo, Department of Economics, 2005)
In the period from 1970 to 2002, Norwegian women moved out of the home and into the paid labour market. The paper investigates the e®ect of this social change on women's economic position and on individual income in-equality. It argues that the distribution of individual incomes is of equal interest to household incomes as targets of public policy. Inequality is measured by the generalised entropy measure. The data are taken from the triennial, later annual, surveys of income carried out by Statistics Norway in the period, giving reliable data on income for samples varying from 6000 to 30 000 women and men. Women's average income relative to that of men increased from 27 percent to 60 per cent. Total individual income inequality decreased strongly from 1970 to 1990, and decreased very slightly from 1990 to 2002. But this total covers very di®erent developments for women and men. Women's internal inequality decreased up to about 1990; the later trend is unclear. Men's internal inequality increased during the 1990s. However, the increase in men's inequality is shown to be mostly due to °uctuations in capital income. Inequality of employees remained unchanged during the whole period, both for women and men, when capital income is disregarded.
Keywords: D31; 330; Income distribution; Women; Frauen; Einkommensverteilung; Schätzung; Norwegen